O Conceito filosófico de natureza como fundamento da Educação Ambiental: uma contribuição para a melhoria da saúde pública - Dias, Denise Gamio (2011)
This thesis arose from a work experience in public health in the community Cohab Tablada, in Pelotas-RS. It has been proved, then, the need for further study and in the area of Environmental Education - a field full of scientific gaps and misconceptions - through philosophy, to provide a foundation for environmental education as a field of knowledge, and its advance, and therefore, the improvement of public health in communities across the glimpse of the environmental component of health, expressed par excellence in health prevention. The methodology used was theoretical and philosophical research, in order to explain theoretically that the field of environmental education has a significant reductionism in its actions in line with the conception of the nature of modernity. The work is directed to the emergence of attitudes of awareness towards nature, so that might reveal the inner nature always present in humans. This awakening of sensibility approaching the two fields of knowledge - health and environmental education, being a bridge par excellence - sensibility - which will recover lost / repressed / forgotten items about the split man / nature occurred, most dramatically, in modern times. This work aims at giving a bestowmwnt to actions / experiences that ensure the environmental component of health in communities, developing environmental education activities that contribute to the prevention and mitigation of diseases and other health problems, establishing conditions to ensure the universalness of the actions and of environmental health services related to Public Health